ROCKing Regeneration: Rho Kinase Inhibition as Molecular Target for Neurorestoration - Tönges, Lars; Koch, Jan C.; Bähr, Mathias; Lingor, Paul (Frontiers in Molecular Neuroscience, 2011)
Regenerative failure in the CNS largely depends on pronounced growth inhibitory signaling and reduced cellular survival after a lesion stimulus. One key mediator of growth inhibitory signaling is Rho-associated kinase (ROCK), which has been shown to modulate growth cone stability by regulation of actin dynamics. Recently, there is accumulating evidence the ROCK also plays a deleterious role for cellular survival. In this manuscript we illustrate that ROCK is involved in a variety of intracellular signaling pathways that comprise far more than those involved in neurite growth inhibition alone. Although ROCK function is currently studied in many different disease contexts, our review focuses on neurorestorative approaches in the CNS, especially in models of neurotrauma. Promising strategies to target ROCK by pharmacological small-molecule inhibitors and RNAi approaches are evaluated for their outcome on regenerative growth and cellular protection both in preclinical and in clinical studies.